Determining factors for the design and implementation of a Virtual Guide in tourist destinations (Research, Society and Development, 2024)
Worldwide, sustainable tourism has become a crucial approach to addressing the challenges of unchecked tourism growth. This research aims to identify the factors determining the design and implementation of a virtual guide for tourist destinations. The study was conducted in the Bolívar canton, Manabí province, Ecuador, using analytical-synthetic and descriptive methods, combining bibliographic review, inventory sheets for tourist resources and attractions, and interviews with 10 key sector stakeholders. The results revealed that the canton has a diverse tourism offer, including 18 natural attractions, 13 hotels, 47 restaurants, and 9 tourist centers. Based on expert criteria, 11 determining factors for the guide were identified, notably the personalized prototype (Avatar), the chatbot, and integration with meta-search engines. In conclusion, Bolívar canton has a wide range of natural and cultural resources that, through the virtual tourist guide, will be enhanced to attract new visitors and establish the canton as a prominent tourist destination.